2015
DOI: 10.1039/c5ta00321k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a calcium-bridged siloxene by a solid state reaction for optical and electrochemical properties

Abstract: A Ca-bridged siloxene resulting from the deintercalation of Ca from CaSi2was synthesized, which shows stable Li storage performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…In addition, Ca‐rich regions would be partially Ca‐extracted CaSi 2 particles (Figures c and ). These particles would not be detected by XRD measurement because Ca extraction induced structural disorder . The average Ca:Si ratio was 0.29:2 and the amount of Cl was less than 0.1 at% for the entire region of the SEM image in Figure (A).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Ca‐rich regions would be partially Ca‐extracted CaSi 2 particles (Figures c and ). These particles would not be detected by XRD measurement because Ca extraction induced structural disorder . The average Ca:Si ratio was 0.29:2 and the amount of Cl was less than 0.1 at% for the entire region of the SEM image in Figure (A).…”
Section: Resultsmentioning
confidence: 98%
“…The dangling bonds or the surface of the formed siloxene are reactive. Siloxene may also have introduced an advantage as a mixing counter partner with Cu 2 O because siloxene is a semiconductor with photocatalytic activity and anode performance for Li ion batteries …”
Section: Introductionmentioning
confidence: 99%
“…The higher deposition rate of Ca than the conventional RDE, control of the annealing temperature to induce the Kirkendall effect, and the choice of the growth surface play important roles to obtain the ordered microwalls. CaSi 2 powders are known as raw materials for the fabrication of functional Si‐based nanomaterials with characteristic electrochemical and optical properties . Si‐based nanosheets attached firmly on the current collector are desired as electrode materials for secondary batteries because a reduction of the electrical contact resistance is expected.…”
Section: Discussionmentioning
confidence: 99%
“…The layered CaSi 2 is transformed, based on the Ca extraction reactions, into organic‐modified Si nanosheets and Si‐based nanoflake particles . In a previous report, it was shown that nanoflakes aggregated with slit‐like nanopores were prepared by using layered CaSi 2 powders (particle size <32 μm) as a raw material and that they exhibited nanostructure‐derived characteristic properties such as an excellent anode performance in Li‐ion batteries and a broad absorption tail ranging from visible to ultraviolet wavelengths . For battery applications, electrode materials attached firmly on the current collector are desired to reduce the electrical contact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The common method to prepare siloxene is the deintercalation of Ca atom by different oxidant (metal chlorides, I 2 , aqueous HCl, etc. )34,35 from CaSi 2 , which is a hexagonal layered structure consisting of alternating Ca layers and corrugated Si (111) planes 36. In the fields of solar‐electric energy conversion37 and lithium storage,38,39 siloxene has been demonstrated as an efficient metal‐free semiconductor for photocatalytic water‐splitting, and an excellent anode material for Li‐ion batteries.…”
Section: Introductionmentioning
confidence: 99%